Two clothes of the same person: a personal and scientific discovery and journey living with bipolar disorder / Wv - Wv, Wv (Universiti Teknologi MARA, Negeri Sembilan, 2024)
I am WV, and my journey with bipolar disorder began in late December of 2017. Over the past seven years, I have explored the sunshine and rainbows of mania and weathered the rain and ruin of depression, with each brief passing experience of highs and lows, weaving a unique thread with its colour and hues on the tapestry of my life, making myself into a barren and beautiful patchwork of a person. In this intimate account, I will intertwine and untangle personal reflections and refractions with scientific insights, offering a glimpse into the complexity of the flora and fauna, the biome of bipolar disorder.